Holistic approach to restore marine ecosystems: RENOVATE project - Marco Marcelli; Sergio Scanu; Daniele Piazzolla; Simone Bonamano; Alice Madonia; Giorgio Fersini; Viviana Piermattei; Mar Bosch-Belmar; Francesco Paolo Mancuso; Giulia Ceccherelli; Annalisa Falace; Paola Del Negro; et al. (Frontiers in Marine Science, 2026)
Mediterranean coastal ecosystems are increasingly threatened by multiple anthropogenic pressures and climate change. As a result, these impacts have caused the decline of key endemic habitats such as Posidonia oceanica meadows and coralligenous reefs. Due to the slow natural recovery of these habitats after degradation, restoration actions play a key role in accelerating ecosystem recovery, reestablishing ecological structure and functional processes, and preventing further biodiversity and ecosystem service loss. Given the frequent habitat fragmentation and high levels of endemism, effective restoration efforts require a multidisciplinary, ecosystem-based approach that integrates marine science, engineering, socioeconomics, and policy. This study describes the holistic approach adopted in the RENOVATE project, which established an integrated framework to address the combined impacts of climate change and human pressures on vulnerable ecosystems. The framework employs advanced observational technologies, field data, and numerical modeling within an adaptive management loop, enabling site-specific, evidence-based restoration planning and assessment of ecosystem services recovery. Additionally, the study reports results from the northern Tyrrhenian coast (Latium, Italy), where RENOVATE aims to protect EU priority habitats and species from human pressures and climate-related threats. Although project activities are still in early stages, results from active restoration in the northern Latium coast show initial establishment and survival at pilot sites, highlighting the framework’s potential to guide effective, replicable interventions in coastal ecosystems. Beyond the regional case study, the proposed framework contributes to global marine restoration efforts by providing a transferable methodology for the management of coastal ecosystems.

Habitat suitability model for predicting the occurrence of scleractinian cold-water corals in the Gulf of Naples (Tyrrhenian Sea): A tool for restoration planning and governance of deep-sea ecosystems - Fabio Di Giovanna; Giorgio Castellan; Michela Angiolillo; Vincenzo Botte; Simonetta Fraschetti; Valentina Grande; Daniele Iudicone; Florian Kokoszka; Paolo Montagna; Mariacristina Prampolini; Giorgio Simone; Marco Taviani; et al. (Marine Environmental Research, 2026)

The Italian effort toward a coordinated observation of Essential Variables (EOV, ECV, EBV) in European Marine Environments. Long-term observation in the central Mediterranean seas and Italian coasts - Simone Toller; Emilio Urbinati; Debora Bellafiore; Caterina Bergami; Francesca De Pascalis; Marcello G. Magaldi; Marco Bellacicco; Federico Bellati; Maristella Berta; Angelo Boccacci; Roberto Bozzano; Fabio Brunetti; et al. (Frontiers in Marine Science, 2026)
Monitoring Essential Ocean, Climate, and Biodiversity Variables (EOVs, ECVs and EBVs) collected through the marine Research Infrastructures (RIs) is critical for assessing environmental status, improving scientific knowledge and defining environmental policies. This study evaluates the capacity of the Italian marine monitoring system, including facilities such as fixed stations, buoys, autonomous platforms, and mobile systems across the Mediterranean Sea, to produce those variables. Conducted in 2023 within the framework of the ITINERIS project ( https://itineris.cnr.it/ ), which aims to strengthen coordination among national and ESFRI RIs (European Strategy Forum on Research Infrastructures), the analysis systematically examines the spatial, thematic, and technological coverage of EOVs, ECVs, EBVs observations and their alignment with international standards for environmental monitoring of 155 facilities from eight Italian and pan-European marine RIs. Of the 107 EVs recognized, 50% were actively produced by the RIs considered, with over 90% meeting the established requirements for EVs. These numbers will be updated to reflect the new equipment acquired during the project’s implementation up to early 2026, which is expected to boost EVs production by approximately 38-40%. The national monitoring network demonstrates a high degree of maturity for oceanic and climate variables, while biodiversity observations remain less represented, indicating the need for further technological innovation and automation. These findings emphasize the importance of enhancing coordination and harmonization among RIs to ensure balanced and interoperable monitoring. The study provides key recommendations to strengthen Italy’s capacity to contribute to the global characterization of EOVs, ECVs, and EBVs and to support evidence-based environmental assessments and the development of robust environmental management strategies at European level.

Trees control hillslope subsurface flow: Insights from stemflow and throughfall experiments, geophysical surveys, and numerical modeling - Simone Di Prima; Gersende Fernandes; Maria Burguet; Maria Paz Salazar; Elisa Marras; Ilenia Murgia; Konstantinos Kaffas; Luca Peruzzo; Ryan D. Stewart; Majdi R. Abou Najm; Alessandro Comegna; Laurent Lassabatere; et al. (Journal of Hydrology, 2026)

Bioapatite crystallinity and Rare Earth Element signatures in fossil and Recent sharks: A window into Past and Present seas - Luca Medici; Annalisa Ferretti; Alberto Collareta; Giulia Bosio; Giovanni Bianucci; Giorgio Carnevale; Simone Casati; Simona Clò; Luca Lanteri; Federico Lugli; Giuseppe Marramà; Frederik H. Mollen; et al. (Chemical Geology, 2026)

Switching between ordinary and non-ordinary activity at Stromboli volcano: insights from short- and long-term thermal trends recorded from space - Marco Laiolo; Diego Coppola; Simone Aveni; Adele Campus; Francesco Massimetti; Alessandro Aiuppa; Lorenzo Innocenti; Giorgio Lacanna; Giovanni Lo Bue Trisciuzzi; Marco Pistolesi; Maurizio Ripepe; Marija Voloschina (Bulletin of Volcanology, 2026)
Ordinary, moderately explosive activity at Stromboli is sporadically interrupted by larger effusive and explosive events that can trigger hazardous phenomena such as sector collapses, tsunamis, and ballistic fallout. We analyze 25 years of satellite infrared data to characterize the thermal pattern associated with these larger events, including: (1) effusive eruptions, (2) lava overflows, (3) major explosions, and (4) paroxysms. Increased heat flux precedes effusive eruptions and overflow sequences, and is interpreted to reflect the progressive rise of the magma column in the conduit accompanying the transition between Strombolian and effusive regimes. Conversely, major explosions are not preceded by any detectable thermal increase, although they statistically occur during periods of frequent overflows in which the Volcanic Radiative Power (VRP) is punctuated by higher values. Paroxysms (which occurred at the beginning, during and at the end of the effusive eruptions) do not show systematic thermal patterns in the preceding days, but in most cases are followed by a VRP increase. Major explosions and paroxysmal events contribute minimally to the long-term energy released by the volcano. Instead, the energy output is primarily governed by the recurrent transitions between Strombolian- and effusive-dominated regimes, sustaining a long-term, steady-state VRP of approximately 14.5 MW. Overall, only ~ 25% of the thermal energy is radiated during Strombolian activity, whereas overflows and effusions account for ~ 15% and ~ 60%, respectively. Results highlight that satellite thermal analysis is a useful tool for tracking changes of surface activity at open-vent basaltic volcanoes with frequent switching from ordinary low-energy activity to more energetic explosive or effusive eruptions.

Ultrafine particles exposure and early subclinical cardiovascular effects from shipping and port activities - Joanna Izabela Lachowicz; Alessandro Murru; Simone Milia; Sergio Pili; Roberta Montisci; Silvia Palomba; Mariusz Jaremko; Maria Francesca Marchetti; Luca Fazzini; Luca Stabile; Giorgio Buonanno; Marcello Campagna; et al. (Science of The Total Environment, 2026)

A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

Application of computer vision for automated detection of different lesions in pig lungs: An exploratory study - Matteo Recchia; Lucia Scuri; Camilla Allegri; Claudia Romeo; Federico Scali; Antonio Marco Maisano; Giovanni Santucci; Giorgio Bontempi; Simone Canesi; Laura Sala; Camilla Recordati; Eugenio Scanziani; et al. (Preventive Veterinary Medicine, 2025)

Heyndrickxia coagulans LMG S-24828 Is a Safe Probiotic Strain Capable of Germinating in the Human Gut - Robin Duncan; Giacomo Mantegazza; Giorgio Gargari; Elena Pierallini; Rosario Russo; Simone Guglielmetti (Probiotics and Antimicrobial Proteins, 2025)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Antibiotics in the aquatic environment. A deep voyage across chemical occurrence data, socio-economic relationships and international policies on antimicrobial consumption and resistance within 2014–2024 - Roberta Rosato; Federica Castellani; Matteo Ricci; Alessia Manucci; Vanessa Di Simone; Giampiero Scortichini; Giorgio Saluti (Science of The Total Environment, 2025)

Correction: Diego-Tortosa et al. Effective Strategies for Automatic Analysis of Acoustic Signals in Long-Term Monitoring. J. Mar. Sci. Eng. 2025, 13, 454 - Dídac Diego-Tortosa; Danilo Bonanno; Manuel Bou-Cabo; Letizia S. Di Mauro; Abdelghani Idrissi; Guillermo Lara; Giorgio Riccobene; Simone Sanfilippo; Salvatore Viola (Journal of Marine Science and Engineering, 2025)
There was an error in the original publication [...]

Taxonomy for conservation: multi-taxa survey evidences a biodiversity hotspot in the Central Apennines (Salto-Cicolano District) - Pierangelo Crucitti; Danilo Russo; Giovanni Amori; Marcello Vitale; Corrado Battisti; Roberto Antonelli; Davide Brocchieri; Marco Giardini; Luigi Lenzini; Paolo Mazzei; Nicolò Pellecchia; Luca Tringali; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

An interpretable and transferable model for shallow landslides detachment combining spatial Poisson point processes and generalized additive models - Giulia Patanè; Teresa Bortolotti; Vasil Yordanov; Ludovico Giorgio Aldo Biagi; Maria Antonia Brovelli; Xuan Quang Truong; Simone Vantini (Stochastic Environmental Research and Risk Assessment, 2025)
Shallow landslides are rapidly moving and strongly dangerous slides. In the present work, the probabilistic distribution of the landslide detachment points within a valley is modelled as a spatial Poisson point process, whose intensity depends on geophysical covariates according to a generalized additive model. This jointly allows to obtain good predictive performance and to preserve the interpretability of the effects of the geophysical predictors on the intensity of the process. We propose a novel workflow, based on Random Forests, to select the geophysical predictors entering the model for the intensity. The statistically significant effects are interpreted as activating or stabilizing factors for landslide detachment. The transferability of the resulting model is guaranteed by training, validating and testing the algorithms on mutually disjoint valleys in the Alps of Lombardy (Italy). Finally, the uncertainty around the estimated intensity of the process is quantified via semiparametric bootstrap.

Detection of Seismic and Acoustic Sources Using Distributed Acoustic Sensing Technology in the Gulf of Catania - Abdelghani Idrissi; Danilo Bonanno; Letizia S. Di Mauro; Dídac Diego-Tortosa; Clara Gómez-García; Stephan Ker; Florian Le Pape; Shane Murphy; Sara Pulvirenti; Giorgio Riccobene; Simone Sanfilippo; Salvatore Viola (Journal of Marine Science and Engineering, 2025)
Distributed Acoustic Sensing (DAS) technology presents an innovative method for marine monitoring by adapting existing underwater optical fiber networks. This paper examines the use of DAS with the Istituto Nazionale di Fisica Nucleare–Laboratori Nazionali del Sud (INFN-LNS) optical fiber infrastructure in the Gulf of Catania, Eastern Sicily, Italy. This region in the Western Ionian Sea provides a unique natural laboratory due to its tectonic and volcanic activity, proximity to Mount Etna, diverse marine ecosystems and significant human influence through maritime traffic. By connecting a 28 km long optical cable to an Alcatel Submarine Network OptoDAS interrogator, DAS successfully detected a range of natural and human–made signals, including a magnitude 3.5 ML earthquake recorded on 14 November 2023, and acoustic signatures from vessel noise. The earthquake–induced Power Spectral Density (PSD) increased to up to 30 dB above background levels in the 1–15 Hz frequency range, while vessel noise exhibited PSD peaks between 30 and 60 Hz with increases of up to 5 dB. These observations offered a detailed spatial and temporal resolution for monitoring seismic wave propagation and vessel acoustic noise. The results underscore DAS’s capability as a robust tool for the continuous monitoring of the rich underwater environments in the Gulf of Catania.

Effective Strategies for Automatic Analysis of Acoustic Signals in Long-Term Monitoring - Dídac Diego-Tortosa; Danilo Bonanno; Manuel Bou-Cabo; Letizia S. Di Mauro; Abdelghani Idrissi; Guillermo Lara; Giorgio Riccobene; Simone Sanfilippo; Salvatore Viola (Journal of Marine Science and Engineering, 2025)
Hydrophones used in Passive Acoustic Monitoring generate vast amounts of data, with the storage requirements for raw signals dependent on the sampling frequency, which limits the range of frequencies that can be recorded. Since the installation of these observatories is costly, it is crucial to maximize the utility of high-sampling-rate recordings to expand the range of survey types. However, storing these large datasets for long-term trend analysis presents significant challenges. This paper proposes an approach that reduces the data storage requirements by up to 85% while preserving critical information about Power Spectral Density and Sound Pressure Level. The strategy involves generating these key metrics from spectrograms, enabling both short-term (micro) and long-term (macro) studies. A proposal for efficient data processing is presented, structured in three steps: the first focuses on generating key metrics to replace space-consuming raw signals, the second addresses the treatment of these metrics for long-term studies, and the third outlines the creation of event detectors from the processed metrics. A comprehensive overview of the essential features for analyzing acoustic signals is provided, along with considerations for the future design of marine observatories. The necessary calculations and processes are detailed, demonstrating the potential of these methods to address the current data storage and processing limitations in long-term acoustic monitoring.

Time and climate roles in driving soil carbon distribution and stability in particulate and mineral-associated organic matter pools - Giorgio Galluzzi; Cesar Plaza; Beatrice Giannetta; Simone Priori; Claudio Zaccone (Science of The Total Environment, 2025)

TNBS colitis induces architectural changes and alpha-synuclein overexpression in mouse distal colon: A morphological study - Arianna Casini; Giorgio Vivacqua; Ludovica Ceci; Stefano Leone; Rosa Vaccaro; Marco Tagliafierro; Filippo Maria Bassi; Sara Vitale; Emanuele Bocci; Luigi Pannarale; Simone Carotti; Antonio Franchitto; et al. (Cell and Tissue Research, 2025)

Clostridioides difficile infections caused by hypervirulent strains: a single-centre real-life study - Giorgio Tiecco; Maria Antonia De Francesco; Angelica Lenzi; Simone Pellizzeri; Francesco Rossini; Alessio Sollima; Liana Signorini; Francesco Castelli; Arnaldo Caruso; Eugenia Quiros-Roldan (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

An early Transcriptomic Investigation in Adult Patients with Spinal Muscular Atrophy Under Treatment with Nusinersen - Maria Liguori; Annalisa Bianco; Alessandro Introna; Arianna Consiglio; Giammarco Milella; Elena Abbatangelo; Eustachio D’Errico; Flavio Licciulli; Giorgio Grillo; Isabella Laura Simone (Journal of Molecular Neuroscience, 2024)
Spinal muscular atrophy (SMA) is a rare degenerative disorder with loss of motor neurons caused by mutations in the SMN1 gene. Nusinersen, an antisense oligonucleotide, was approved for SMA treatment to compensate the deficit of the encoded protein SMN by modulating the pre–mRNA splicing of SMN2 , the centromeric homologous of SMN1 , thus inducing the production of a greater amount of biologically active protein. Here, we reported a 10-month transcriptomics investigation in 10 adult SMA who received nusinersen to search for early genetic markers for clinical monitoring. By comparing their profiles with age-matched healthy controls (HC), we also analyzed the changes in miRNA/mRNAs expression and miRNA-target gene interactions possibly associated with SMA. A multidisciplinary approach of HT-NGS followed by bioinformatics/biostatistics analysis was applied. Within the study interval, those SMA patients who showed some clinical improvements were characterized by having the SMN2/SMN1 ratio slightly increased over the time, while in the stable ones the ratio decreased, suggesting that the estimation of SMN2/SMN1 expression may be an early indicator of nusinersen efficacy . On the other hand, the expression of 38/147 genes/genetic regions DE at T0 between SMA and HC like TRADD and JUND resulted “restored” at T10. We also confirmed the dysregulation of miR-146a(-5p), miR-324-5p and miR-423-5p in SMA subjects. Of interest, miR-146a-5p targeted SMN1 , in line with experimental evidence showing the key role of astrocyte-produced miR-146a in SMA motor neuron loss. Molecular pathways such as NOTCH, NF-kappa B, and Toll-like receptor signalings seem to be involved in the SMA pathogenesis.

Soil organic matter dynamics and stability: Climate vs. time - Giorgio Galluzzi; César Plaza; Simone Priori; Beatrice Giannetta; Claudio Zaccone (Science of The Total Environment, 2024)

Lactic acid bacteria naturally associated with ready-to-eat rocket salad can survive the human gastrointestinal transit - Giacomo Mantegazza; Robin Duncan; Nicolò Telesca; Giorgio Gargari; Susanna Perotti; Patrizia Riso; Simone Guglielmetti (Food Microbiology, 2024)

Phthalate levels in common sea anemone Actinia equina and Anemonia viridis: A proxy of short-term microplastic interaction? - Sara Vencato; Simone Montano; Francesco Saliu; Stefania Coppa; Alessandro Becchi; Immacolata Liotta; Tommaso Valente; Mariacristina Cocca; Marco Matiddi; Andrea Camedda; Giorgio Massaro; Davide Seveso; et al. (Marine Pollution Bulletin, 2024)

Industrial by-products-derived binders for in-situ remediation of high Pb content pyrite ash: Synergistic use of ground granulated blast furnace slag and steel slag to achieve efficient Pb retention and CO2 mitigation - Yikai Liu; Simone Molinari; Maria Chiara Dalconi; Luca Valentini; Maurizio Pietro Bellotto; Giorgio Ferrari; Roberto Pellay; Graziano Rilievo; Fabio Vianello; Alessia Famengo; Gabriella Salviulo; Gilberto Artioli (Environmental Pollution, 2024)

Influence of filtration treatments on grapevine DNA traceability in wine - Jianqiang Song; Camilla De Paolis; Paolo Boccacci; Lorenzo Ferrero; Amedeo Moine; Susana Río Segade; Simone Giacosa; Giorgio Gambino; Luca Rolle; Maria Alessandra Paissoni (Food Bioscience, 2024)

River–coastal–ocean continuum modeling along the Lazio coast (Tyrrhenian Sea, Italy): Assessment of near river dynamics in the Tiber delta - Simone Bonamano; Ivan Federico; Salvatore Causio; Viviana Piermattei; Daniele Piazzolla; Sergio Scanu; Alice Madonia; Nicola Madonia; Giovanni De Cillis; Eric Jansen; Giorgio Fersini; Giovanni Coppini; et al. (Estuarine, Coastal and Shelf Science, 2024)

Marine phycotoxin levels in shellfish—14 years of data gathered along the Italian coast - Stefano Accoroni; Monica Cangini; Roberto Angeletti; Carmen Losasso; Simone Bacchiocchi; Antonella Costa; Aurelia Di Taranto; Laura Escalera; Giorgio Fedrizzi; Angela Garzia; Francesca Longo; Andrea Macaluso; et al. (Harmful Algae, 2024)

Pseudotachylytes in felsic lower-crustal rocks of the Calabrian Serre massif: A record of deep- or shallow-crustal earthquakes? - Simone Papa; Giorgio Pennacchioni; Alfredo Camacho; Kyle P. Larson (Lithos, 2023)

The Evaluation of WaveSAX Power Generation to Support Port Energy Self-Sufficiency - Simone Bonamano; Maximo Aurelio Peviani; Giordano Agate; Calogero Giuseppe Burgio; Giorgio Fersini; Marco Marcelli (Journal of Marine Science and Engineering, 2023)
Remarkable advancements have been made in wave energy converters, notably the innovative WaveSAX technology—an oscillating water column system conceptually designed for coastal structures. Proven effective in existing installations, particularly at Civitavecchia Port, Italy, where the WaveSAX-1 prototype was tested in 2018 and the WaveSAX-2 was updated in 2021. The device’s power generation capacity was evaluated using a Simulating WAves Nearshore (SWAN) model that simulated 30 years of wave conditions. Validation with radar and Acoustic Doppler Profiler instruments showed excellent performance in wave height simulation. Results revealed higher wave power generation near the harbor breakwater, surpassing offshore levels, especially in central and northern sections. WaveSAX-2, featuring an improved Wells turbine, demonstrated a remarkable 37% increase in average efficiency compared to WaveSAX-1. If a linear WaveSAX array were installed, it could produce 4 GWh annually, satisfying 20% of the port’s energy needs and reducing around 2800 tCO2e/year. Doubling arrays and incorporating triangular modules could significantly enhance sustainability for port operations, offering a promising path toward self-sufficiency and environmental responsibility.

Enantiopure β-isocyano-boronic esters: synthesis and exploitation in isocyanide-based multicomponent reactions - Marco Manenti; Simone Gusmini; Leonardo Lo Presti; Giorgio Molteni; Alessandra Silvani (Molecular Diversity, 2023)
Various boron-containing isocyanides have been efficiently synthesized from the corresponding enantiopure β-substituted β-amino boronic acid pinacol esters, without need for protecting group interconversion, through a two-step, purification-free procedure. They were employed in a variety of isocyanide-based multicomponent reactions, proving to be reliable components for all of them and allowing the efficient synthesis of unprecedented, boron-containing peptidomimetics and heteroatom-rich small molecules, including biologically relevant cyclic boronates. Jointing together the β-amido boronic acid moiety, deriving from the isocyanide component, with prominent pharmacophoric rings emerging from the multicomponent process, a successful application of the molecular hybridization concept could be realized. Graphical abstract

Mechanistic insights into Pb and sulfates retention in ordinary Portland cement and aluminous cement: Assessing the contributions from binders and solid waste - Yikai Liu; Simone Molinari; Maria Chiara Dalconi; Luca Valentini; Maurizio Pietro Bellotto; Giorgio Ferrari; Roberto Pellay; Graziano Rilievo; Fabio Vianello; Gabriella Salviulo; Qiusong Chen; Gilberto Artioli (Journal of Hazardous Materials, 2023)

The leaching behaviors of lead, zinc, and sulfate in pyrite ash contaminated soil: mineralogical assessments and environmental implications - Yikai Liu; Simone Molinari; Maria Chiara Dalconi; Luca Valentini; Giulia Ricci; Claudio Carrer; Giorgio Ferrari; Gilberto Artioli (Journal of Environmental Chemical Engineering, 2023)

Quantifying Transgressive Coastal Changes Using UAVs: Dune Migration, Overwash Recovery, and Barrier Flooding Assessment and Interferences with Human and Natural Assets - Giulia Casagrande; Annelore Bezzi; Saverio Fracaros; Davide Martinucci; Simone Pillon; Paolo Salvador; Stefano Sponza; Giorgio Fontolan (Journal of Marine Science and Engineering, 2023)
The advantages derived from the use of Uncrewed Aerial Vehicles (UAVs) are well-established: they are cost-effective and easy to use. There are numerous environmental applications, particularly when monitoring contexts characterized by rapid morphological changes and high rates of sediment transport, such as coastal areas. In this paper, three different case studies of survey and monitoring with high resolution and accuracy obtained through the use of UAVs are presented; these concern transgressive coastal sites. Results allow for the definition and quantification of coastal landforms and processes, including: (i) The anatomy of a parabolic dune and the rate of landward migration that could interfere with a tourist settlement; (ii) The mode and timing of morphological recovery and realignment of a barrier island overwashed by storm surge episodes; and (iii) The potential flood risk of a progradational spit that is a nesting site of a species of migratory breeding birds of conservation concern. The results demonstrate and confirm that, through a good coupling of drone-sensed quality data and accurate topographic control, quantitative estimates that are useful in assessing the impacts of natural processes involving both human and natural assets can be obtained.

Eutrophication history and organic carbon burial rate recorded in sediment cores from the Mar Piccolo of Taranto (Italy) - Janusz Dominik; Simone Leoni; Daniele Cassin; Irene Guarneri; Luca Giorgio Bellucci; Roberto Zonta (Environmental Science and Pollution Research, 2023)
During the second half of the twentieth century, coastal lagoons in densely populated regions experienced eutrophication due to excessive nutrient inputs. Detrimental effects, including hypoxia/anoxia and harmful algae blooms, have occurred in many Mediterranean lagoons, but their trophic evolution is poorly documented. The lack of adequate monitoring data can partly be offset by examining sedimentary records. In the Mar Piccolo, a lagoon comprising two basins near Taranto (Italy), eutrophication has followed population growth and pollution resulting from naval activities and massive industrialisation. Based on 210 Pb-dated sediment cores, continuous in situ density profiles obtained with computed tomography, organic carbon (OC) and total nitrogen (TN) content and OC and TN isotopic signatures, this paper reconstructs the history of eutrophication, discusses the sources of organic matter and provides an estimate of the OC burial rate before and during the eutrophic period. OC burial increased in the period 1928–1935 and peaked in the decade 1960–1970. OC and TN content were still high in the surface sediments collected in 2013, despite partial diversion of sewage outfalls in the period 2000–2005. The divergent δ 13 C and δ 15 N signatures of the two basins during the eutrophic period suggest they were affected by different nutrient sources. The OC burial rate during the eutrophic phase (≈ 46 g m −2 y −1 ) was close to the world median value for lagoon sediments, and was about twice the burial rate recorded in the preceding oligotrophic phase.

Use of kefir-derived lactic acid bacteria for the preparation of a fermented soy drink with increased estrogenic activity - Giacomo Mantegazza; Alessandro Dalla Via; Armando Licata; Robin Duncan; Claudio Gardana; Giorgio Gargari; Cristina Alamprese; Stefania Arioli; Valentina Taverniti; Matti Karp; Simone Guglielmetti (Food Research International, 2023)

Late Quaternary sedimentary record of estuarine incised-valley filling and interfluve flooding: The Manfredonia paleovalley system (southern Italy) - Alessandro Amorosi; Luigi Bruno; Massimo Caldara; Bruno Campo; Simone Cau; Vincenzo De Santis; Andrea Di Martino; Wan Hong; Giorgio Lucci; Claudio Pellegrini; Veronica Rossi; Irene Sammartino; et al. (Marine and Petroleum Geology, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Long-lasting connectivity changes induced by intensive first-person shooter gaming - Davide Momi; Carmelo L. Smeralda; Giorgio Di Lorenzo; Francesco Neri; Simone Rossi; Alessandro Rossi; Emiliano Santarnecchi (Brain Imaging and Behavior, 2021)

Chronic MPTP in Mice Damage-specific Neuronal Phenotypes within Dorsal Laminae of the Spinal Cord - Francesca Biagioni; Giorgio Vivacqua; Gloria Lazzeri; Rosangela Ferese; Simone Iannacone; Paolo Onori; Sergio Morini; Loredana D’Este; Francesco Fornai (Neurotoxicity Research, 2021)
The neurotoxin 1-methyl, 4-phenyl, 1, 2, 3, 6-tetrahydropiridine (MPTP) is widely used to produce experimental parkinsonism. Such a disease is characterized by neuronal damage in multiple regions beyond the nigrostriatal pathway including the spinal cord. The neurotoxin MPTP damages spinal motor neurons. So far, in Parkinson’s disease (PD) patients alpha-synuclein aggregates are described in the dorsal horn of the spinal cord. Nonetheless, no experimental investigation was carried out to document whether MPTP affects the sensory compartment of the spinal cord. Thus, in the present study, we investigated whether chronic exposure to small doses of MPTP (5 mg/kg/X2, daily, for 21 days) produces any pathological effect within dorsal spinal cord. This mild neurotoxic protocol produces a damage only to nigrostriatal dopamine (DA) axon terminals with no decrease in DA nigral neurons assessed by quantitative stereology. In these experimental conditions we documented a decrease in enkephalin-, calretinin-, calbindin D28K-, and parvalbumin-positive neurons within lamina I and II and the outer lamina III. Met-Enkephalin and substance P positive fibers are reduced in laminae I and II of chronically MPTP-treated mice. In contrast, as reported in PD patients, alpha-synuclein is markedly increased within spared neurons and fibers of lamina I and II after MPTP exposure. This is the first evidence that experimental parkinsonism produces the loss of specific neurons of the dorsal spinal cord, which are likely to be involved in sensory transmission and in pain modulation providing an experimental correlate for sensory and pain alterations in PD.

Autozygosity-driven genetic diagnosis in consanguineous families from Italy and the Greater Middle East - Flavia Palombo; Claudio Graziano; Nadia Al Wardy; Nayereh Nouri; Caterina Marconi; Pamela Magini; Giulia Severi; Chiara La Morgia; Gaetano Cantalupo; Duccio Maria Cordelli; Simone Gangarossa; Mohammed Nasser Al Kindi; et al. (Human Genetics, 2020)

On the Flow Past an Array of Two-Dimensional Street Canyons Between Slender Buildings - Maria Grazia Badas; Simone Ferrari; Michela Garau; Alessandro Seoni; Giorgio Querzoli (Boundary-Layer Meteorology, 2020)

Lead and copper in hunted wild boars and radiographic evaluation of bullet fragmentation between ammunitions - Alessandro Menozzi; Simonetta Menotta; Giorgio Fedrizzi; Antonio Lenti; Anna Maria Cantoni; Rosanna Di Lecce; Giacomo Gnudi; Marcos Pérez-López; Simone Bertini (Food Additives & Contaminants Part B-Surveillance, 2019)

Fecal Clostridiales distribution and short‐chain fatty acids reflect bowel habits in irritable bowel syndrome - Giorgio Gargari; Valentina Taverniti; Claudio Gardana; Cesare Cremon; Filippo Canducci; Isabella Pagano; Maria Raffaella Barbaro; Lara Bellacosa; Anna Maria Castellazzi; Chiara Valsecchi; Sara Carlotta Tagliacarne; Massimo Bellini; et al. (Environmental Microbiology, 2018)
Summary Irritable bowel syndrome (IBS), a common functional gastrointestinal disorder, is classified according to bowel habits as IBS with constipation (IBS‐C), with diarrhea (IBS‐D), with alternating constipation and diarrhea (IBS‐M), and unsubtyped (IBS‐U). The mechanisms leading to the different IBS forms are mostly unknown. This study aims to evaluate whether specific fecal bacterial taxa and/or short‐chain fatty acids (SCFAs) can be used to distinguish IBS subtypes and are relevant for explaining the clinical differences between IBS subcategories. We characterized five fecal samples collected at 4‐weeks intervals from 40 IBS patients by 16S rRNA gene profiling and SCFA quantification. Finally, we investigated the potential correlations in IBS subtypes between the fecal microbial signatures and host physiological and clinical parameters. We found significant differences in the distribution of Clostridiales OTUs among IBS subtypes and reduced levels of SCFAs in IBS‐C compared to IBS‐U and IBS‐D patients. Correlation analyses showed that the diverse representation of Clostridiales OTUs between IBS subtypes was associated with altered levels of SCFAs; furthermore, the same OTUs and SCFAs were associated with the fecal cytokine levels and stool consistency. Our results suggest that intestinal Clostridiales and SCFAs might serve as potential mechanistic biomarkers of IBS subtypes and represent therapeutic targets.

Inventory and conservation assessment for the management of coastal dunes, Veneto coasts, Italy - Annelore Bezzi; Simone Pillon; Davide Martinucci; Giorgio Fontolan (Journal of Coastal Conservation, 2018)

Turbulence and Air Exchange in a Two-Dimensional Urban Street Canyon Between Gable Roof Buildings - Michela Garau; Maria Grazia Badas; Simone Ferrari; Alessandro Seoni; Giorgio Querzoli (Boundary-Layer Meteorology, 2018)

Multiclass methods for the analysis of antibiotic residues in milk by liquid chromatography coupled to mass spectrometry: A review - Rosanna Rossi; Giorgio Saluti; Simone Moretti; Irene Diamanti; Danilo Giusepponi; Roberta Galarini (Food Additives & Contaminants: Part A, 2018)

Characterization of the human DNA gut virome across populations with different subsistence strategies and geographical origin - Simone Rampelli; Silvia Turroni; Stephanie L. Schnorr; Matteo Soverini; Sara Quercia; Monica Barone; Andrea Castagnetti; Elena Biagi; Giorgio Gallinella; Patrizia Brigidi; Marco Candela (Environmental Microbiology, 2017)
Summary It is a matter of fact that the human gut microbiome also includes a non‐bacterial fraction represented by eukaryotic cells and viruses. To further explore the gut microbiome variation in human populations, here we characterized the human DNA viral community from publicly available gut metagenome data sets from human populations with different geographical origin and lifestyle. In particular, such data sets encompass microbiome information from two western urban societies (USA and Italy), as well as two traditional hunter‐gatherer communities (the Hadza from Tanzania and Matses from Peru) and one pre‐agricultural tribe (Tunapuco from Peru). Our results allowed for the first taxonomic reconstruction of the complex viral metacommunities within the human gut. The core virome structure included herpesviruses, papillomaviruses, polyomaviruses, adenoviruses and anelloviruses. Using Random Forests and a co‐occurrence analysis approach, we identified the viruses that distinguished populations according to their geographical origin and/or lifestyle. This paves the way for new research aimed at investigating the biological role of the gut virome in human physiology, and the importance of our viral counterpart in the microbiome‐host co‐evolutionary process.

Resilience of European larch (Larix decidua Mill.) forests to wildfires in the western Alps - Jose V. Moris; Giorgio Vacchiano; Simone Ravetto Enri; Michele Lonati; Renzo Motta; Davide Ascoli (New Forests, 2017)

Over 10 years of variation in Mediterranean reef benthic communities - Federico Betti; Giorgio Bavestrello; Marzia Bo; Valentina Asnaghi; Mariachiara Chiantore; Simone Bava; Riccardo Cattaneo‐Vietti (Marine Ecology, 2017)
During the last several decades, the Mediterranean littoral shallow water benthic communities have suffered significant changes in their structure and taxa composition. Despite numerous studies conducted to characterize these changes at various levels, it has always been very difficult to disentangle the effects of natural factors from anthropic ones. The main purpose of this work was to evaluate possible changes, over a 10‐year scale, in diversity and abundance of the most representative species of the benthic communities considered to be primarily and potentially affected by natural stressors in a highly protected area. Sets of macro‐photographs were taken in 2002–2003 of three sites inside a small bay called Ca’ dell'Oro, which is the “no entry—no take” zone of the Marine Protected Area of Portofino, in order to analyse the structure of the benthic communities at different depths over a short time scale. The same sampling was repeated 10 years later in 2013. In the 10‐year span, a significant change in the macroalgal coverage and composition was observed, while the overall richness and coverage of species remained almost unchanged. This process resulted in a significant reduction of the habitat complexity of the three‐dimensional algal components. Likewise, a remarkable change in terms of presence and abundance occurred among all zoobenthic components. The benthic communities seem to have suffered from detrimental effects probably caused by climatic events that have been occurring in recent years in the Ligurian Sea.

Long-term life cycle and massive blooms of the intertidal hydroid Paracoryne huvei in the North-western Mediterranean Sea - Federico Betti; Giorgio Bavestrello; Carlo Nike Bianchi; Carla Morri; Elena Righetti; Simone Bava; Marzia Bo (Marine Biology Research, 2017)

Evaporative demand determines the relative transpirational sensitivity of deficit-irrigated grapevines - Uri Hochberg; Jose Carlos Herrera; Asfaw Degu; Simone Diego Castellarin; Enrico Peterlunger; Giorgio Alberti; Naftali Lazarovitch (Irrigation Science, 2017)

Evidence of a bacterial core in the stored products pest Plodia interpunctella : the influence of different diets - Matteo Montagna; Valeria Mereghetti; Giorgio Gargari; Simone Guglielmetti; Franco Faoro; Giuseppe Lozzia; Daria Locatelli; Lidia Limonta (Environmental Microbiology, 2016)
Summary The potential influence of insects' feeding behaviour on their associated bacterial communities is currently a matter of debate. Using the major pest of commodities, Plodia interpunctella , as a model and adopting a culture‐independent approach, the impact of different diets on the host‐associated microbiota was evaluated. An analysis of similarity showed differences among the microbiotas of moths fed with five substrates and provided evidence that diet represents the only tested factor that explains this dissimilarity. Bacteria shared between food and insects provide evidence for a limited conveyance to the host of the bacteria derived from the diet; more likely, the content of carbohydrates and proteins in the diets promotes changes in the insect's microbiota. Moth microbiotas were characterized by two robust entomotypes, respectively, associated with a carbohydrate‐rich diet and a protein‐rich diet. These results were also confirmed by the predicted metagenome functional potential. A core microbiota, composed of six taxa, was shared between eggs and adults, regardless of the origin of the population. Finally, the identification of possible human and animal pathogens on chili and associated with the moths that feed on it highlights the possibility that these bacteria may be conveyed by moth frass.

Evaluation of Molecular Markers and Analytical Methods Documenting the Occurrence of Mustard Gas and Arsenical Warfare Agents in Soil - Alessandro Sassolini; Giampaolo Brinchi; Antonio Di Gennaro; Simone Dionisi; Carola Dominici; Luca Fantozzi; Giorgio Onofri; Rosario Piazza; Maurizio Guidotti (Bulletin of Environmental Contamination and Toxicology, 2016)

Seasonal differences in climate in the Chianti region of Tuscany and the relationship to vintage wine quality - Michael James Salinger; Marina Baldi; Daniele Grifoni; Greg Jones; Giorgio Bartolini; Stefano Cecchi; Gianni Messeri; Anna Dalla Marta; Simone Orlandini; Giovanni A. Dalu; Gianpiero Maracchi (International Journal of Biometeorology, 2015)

Recent trends in seasonal and annual precipitation indices in Tuscany (Italy) - Giorgio Bartolini; Alessandro Messeri; Daniele Grifoni; Daniele Mannini; Simone Orlandini (Theoretical and Applied Climatology, 2014)

A real-scale soil phytoremediation - Cristina Macci; Serena Doni; Eleonora Peruzzi; Simone Bardella; Giorgio Filippis; Brunello Ceccanti; Grazia Masciandaro (Biodegradation, 2013)

Determination of macrocyclic lactones in food and feed - Roberta Galarini; Giorgio Saluti; Simone Moretti; Danilo Giusepponi; Guglielmo Dusi (Food Additives & Contaminants: Part A, 2013)

Benthic diatom assemblages and their response to human stress in small-sized volcanic-siliceous streams of central Italy (Mediterranean eco-region) - Valentina Della Bella; Giorgio Pace; Mariachiara Barile; Andrea Zedde; Camilla Puccinelli; Simone Ciadamidaro; Pier Paolo Danieli; Paolo Andreani; Francesca Anna Aulicino; Carlo Belfiore; Laura Mancini (Hydrobiologia, 2012)

Mediterranean warming is especially due to summer season - Giorgio Bartolini; Valentina di Stefano; Giampiero Maracchi; Simone Orlandini (Theoretical and Applied Climatology, 2012)

Recent trends in Tuscany (Italy) summer temperature and indices of extremes - Giorgio Bartolini; Marco Morabito; Alfonso Crisci; Daniele Grifoni; Tommaso Torrigiani; Martina Petralli; Giampiero Maracchi; Simone Orlandini (International Journal of Climatology, 2008)
In the past few decades, many studies showed a significant worldwide warming, and consequently, changes in frequency and persistence of extreme high‐temperature events were observed. In order to analyse summer Tuscany (Italy) patterns of climate change during the period 1955–2004, indices of temperature and of extreme events were investigated for evidence of trend and change in inter‐annual variability by using data of 40 weather stations. Least square regression analysis and Theil‐Sen nonparametric regression were applied for evidence of trends. The Mann–Kendall test was applied to each time series to look for statistically significant trends. The results showed a general increase in minimum and maximum temperatures and extreme temperature events. Maximum temperature increase (+0.44 °C/decade) was slightly greater than minimum temperature (+0.38 °C/decade) and consequently, an increase in summer daily temperature range (DTR) was noted (+0.06 °C/decade). Inter‐annual summer climate variability showed an increasing trend in the whole region, especially in regard to extreme event occurrences while a small decreasing trend concerning diurnal temperature range was observed. Copyright © 2008 Royal Meteorological Society

The C 4 biochemical pathway, and the anatomy of lemongrass ( Cymbopogon citratus (DC) Stapf.) cultivated in temperate climates - Cinzia Margherita Bertea; Giorgio Buffa; Wanda Camusso; Simone Bossi; Silvano Scannerini; Massimo Maffei; Manuela Tesio; Giovanni D'Agostino; Marco Mucciarelli (Plant Biosystems, 2003)

Evidence for a C 4 NADP-ME photosynthetic pathway in Vetiveria zizanioides Stapf - Cinzia M. Bertea; Silvano Scannerini; Wanda Camusso; Simone Bossi; Giorgio Buffa; Massimo Maffei; Giovanni D'Agostino; Marco Mucciarelli (Plant Biosystems, 2001)

Genotoxic and mono-oxygenase system effects of the fungicide maneb - Simone Bertini; Renata Del Carratore; Mario Giorgi; Giorgio Bronzetti; Clara Della Croce (Archives of Toxicology, 2000)